A Systematic Review of Social Media and Government in the Social Science Discipline - Rossi Maunofa Widayat; Juhari Sasmito Aji; Cahyadi Kurniawan (Journal of Contemporary Governance and Public Policy, 2023)
The technical viewpoint recognises the critical role of information and communication technology as a driving force in our time. The importance of public policy management in the environment of public service institutions and regional commands is investigated from the standpoint of public administration and the use of social media. Academics need to map out ideas about how social media and government interact. This research aims to see the important themes or issues raised by scholars in social media and their government articles. What are the comprehensive factors that influence the use of social media in government circles? The research method used was a literature review on social media and government by reviewing journal articles on social media and government published in Scopus as data-based and processed using the NVivo 12 Plus analysis tool. The results of this study reveal five significant problems between social media and the government. These problems include digital difficulties, policies, information, communication, and politics. This research also gave birth to social media and government, which must take the form of digital activism; secondly, access to information disseminated by the government through social media; and third, administrative communication, which looks at how ideas are offered via social media to the government. Fourth, to achieve social media and government goals, it is necessary to demonstrate ethical and political behaviour, formulate policies following those goals, and then evaluate those policies through the implementation of rules or laws.